Building readiness for sustainable health tourism: The influence of workplace well-being climate, eustress, and personal health orientation - Ahmed Mohamed Hasanein; Hazem Ahmed Khairy (African Journal of Hospitality, Tourism and Leisure, 2026)
Grounded in Job Demands-Resources (JD-R) Theory, this study investigates how workplace well-being climate enhances employee readiness for sustainable health tourism through the mediating role of eustress and the moderating role of personal health orientation. The study was conducted among employees working in Egyptian spa and wellness resorts who are directly involved in delivering health and well-being services. Data were collected from 260 employees and analyzed using PLS-SEM with WarpPLS 8.0. The findings indicate that workplace well-being climate significantly promotes employee readiness for sustainable health tourism and positively influences eustress. Eustress, in turn, enhances employee readiness and partially mediates the relationship between workplace well-being climate and readiness. In addition, personal health orientation strengthens the positive effect of workplace well-being climate on eustress, indicating that employees with stronger health orientation derive greater motivational benefits from a supportive work environment. By integrating organizational and personal resources within the JD-R framework, this study extends the literature on sustainable health tourism and employee readiness. The findings also provide practical insights for spa and wellness organizations seeking to foster sustainable transformation through well-being-focused workplace practices.